2010
DOI: 10.1007/s00213-010-1945-1
|View full text |Cite
|
Sign up to set email alerts
|

A within-subject cognitive battery in the rat: differential effects of NMDA receptor antagonists

Abstract: NMDA receptor-dependent mechanisms are requisite in the acquisition of a simple conditional discrimination and consolidation of extinction. Their role in working memory and reversal tasks appear to be less critical and potentially specific to the paradigm and NMDA receptor antagonist used. It is clearly misleading to generalise across NMDA antagonists with respect to their preclinical cognitive profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 62 publications
9
38
0
1
Order By: Relevance
“…Such an interpretation would be more consistent with the markedly inhibitory profile of these compounds on instrumental responding (Gilmour et al 2009) and increases in response latencies and omissions in the absence of any negative impact on accuracy in the DMTP task. However, previous work has shown that NVP-AAM077 is relatively ineffective at blocking both acquisition and extinction of a visuo-auditory discrimination, whilst memantine clearly blocks both of these effects in this task (Dix et al 2010) at doses that decrease response latencies in the present 5CSRT, consistent with findings of mnemonic deficits in otherwise normal animals by others (Creeley et al 2006). Also consistent with this are reports of deficits in recognition memory in normal humans given memantine (Rammsayer 2001).…”
Section: Memantine and Nvp-aam077supporting
confidence: 91%
See 2 more Smart Citations
“…Such an interpretation would be more consistent with the markedly inhibitory profile of these compounds on instrumental responding (Gilmour et al 2009) and increases in response latencies and omissions in the absence of any negative impact on accuracy in the DMTP task. However, previous work has shown that NVP-AAM077 is relatively ineffective at blocking both acquisition and extinction of a visuo-auditory discrimination, whilst memantine clearly blocks both of these effects in this task (Dix et al 2010) at doses that decrease response latencies in the present 5CSRT, consistent with findings of mnemonic deficits in otherwise normal animals by others (Creeley et al 2006). Also consistent with this are reports of deficits in recognition memory in normal humans given memantine (Rammsayer 2001).…”
Section: Memantine and Nvp-aam077supporting
confidence: 91%
“…All doses refer to the base weights of compounds. Doses and routes of administration were chosen on the basis of previously conducted studies (Gilmour et al 2009;Dix et al 2010) and a general assessment of existing published literature in this field.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these previous studies, CP-101,606 was effective at reducing haloperidol-induced catalepsy and neuropathic pain in rats over the dose range (2-20 mg/kg) used in the present study. Furthermore, comparative effects of ketamine and CP-101,606 over the dose ranges used in this study in a number of different behavioral paradigms have also been reported (Dix et al, 2010;Gilmour et al, 2012;Smith et al, 2011).…”
Section: Drug Treatmentmentioning
confidence: 70%
“…This is not to say that GluN2B-containing NMDA receptors do not contribute at all to certain forms of discrimination learning. Indeed, more complex discriminations that require multiple days of training to achieve asymptotic performance and have longer consolidation periods may be more sensitive to GluN2B receptor blockade (Dix et al 2010). Indeed, when learning takes place over several days, mice lacking GluN2B receptors in the forebrain show significant impairments in cortico-hippocampal-dependent tasks (von Engelhardt et al 2008;Brigman et al 2010).…”
Section: Discussionmentioning
confidence: 98%